The Effect of Stress, Dietary Patterns, and Body Mass Index on The Incidence of Hypertension among Patients at Denkesyah Clinic, Madiun, East Java - Lasito; Nurwijayanti; Rahmania Ambarika (Ficco Scientific Corner, 2025)
Background: Hypertension remains a major global health problem and one of the leading risk factors for cardiovascular disease. Both non-modifiable and modifiable factors, such as stress, diet, and obesity, play a crucial role in its development. In Indonesia, hypertension continues to account for a high burden of morbidity, with an increasing prevalence reported in Madiun. This study aimed to analyze the association of stress, dietary patterns, and body mass index (BMI) with hypertension among patients at Denkesyah Clinic, Madiun, East Java. Methods: This study employed a cross-sectional study conducted at Denkesyah Clinic, Madiun, East Java, in October 2024. A total of 87 respondents were selected using purposive sampling from patients enrolled in the chronic disease management program (Prolanis). Data on stress were collected using the Self Reporting Questionnaire-20 (SRQ-20), dietary patterns were assessed with a Food Frequency Questionnaire (FFQ), and body mass index (BMI) was calculated using weight and height measurements. Hypertension was defined as systolic blood pressure ≥140 mmHg and/or diastolic ≥90 mmHg. Data analysis included univariate, bivariate (Chi-square test), and multivariate logistic regression. Results: The study found that 52.9% of respondents experienced high stress levels, 59.8% had poor dietary patterns, and 44.8% were obese. Stress, poor dietary pattern, and elevated BMI were all significantly associated with hypertension (p < 0.05). Multivariate analysis showed that BMI was the most dominant risk factor, with an odds ratio indicating that obese individuals were more likely to develop hypertension compared to those with normal BMI. Conclusions: Stress, dietary pattern, and BMI significantly are associated with hypertension, with BMI being the strongest predictor. Public health interventions should focus on promoting healthy dietary habits, stress management, and weight control strategies to reduce the burden of hypertension in the community.